Transformative Learning: Exploring Project Based Learning into Paragraph Writing - Puspita, Nurul (Universitas Muhammadiyah Tangerang, 2025)
Project-Based Learning (PBL) is a teaching method that contains students in enthusiastically involving with real-life, individualized significance projects. This method allows students to foster their knowledge and skills. Those characteristics are necessary for the students. Therefore, this research examines the implementation of Project-Based Learning (PjBL) in teaching definition paragraph writing, using a qualitative research approach. The research emphasizes comprehending how PBL improves students' appointment, teamwork, and writing skills by focusing on challenges encountered through its implementation. Data were collected through observations and interviews. The findings expose that PjBL raises energetic involvement and critical thinking, allowing students to construct well-organized and expressive definition paragraphs. Though the research also points to challenges like students' problems in familiarizing themselves with collaborative tasks, time management issues, and the need for clear guidance. These results recommend that whereas PjBL is an active method of teaching paragraph writing, its success rests on structured planning and continuous support from educators. The research underwrites the cultivating body of information on participating PjBL into writing instruction, providing practical understandings for increasing teaching methods and student results.